The Taj Mahal. - Carroll, David (New York Newsweek, 1972)
The Taj Mahal is a new volume in the Newsweek Book Devisions series of illustrated histories, wonders of man. Each of these volumes, focusing on a well-known historical monument is divided into three major sections: a lively and informative history of the monument by a distinguished and authoritative writer.
Keywords: Country Studies